Autologous Dermal Fibroblast Injections Slow Atrioventricular Conduction and Ventricular Rate in Atrial Fibrillation in Swine. (April 2015) - Tondato, Fernando; Zeng, Hong; Goodchild, Traci; Ng, Fu Siong; Chronos, Nicolas; Peters, Nicholas S.
<x xml:space="preserve">Abstract</x> Background— Nonpharmacological ventricular rate control in atrial fibrillation (AF) without producing atrioventricular (AV) block remains a clinical challenge. We investigated the hypothesis that autologous dermal fibroblast (ADF) injection into the AV nodal area would reduce ventricular response during AF without causing AV block. Methods and Results— Fourteen pigs underwent electrophysiology study before, immediately, and 28 days after ≈200 million cultured ADFs (n=8) or saline (n=6) were injected under electroanatomical guidance in the AV nodal area, with continuous 28-day ECG recording. In the ADF group at 28 days postinjection, there were prolongations of PR interval (after versus before: 130±13 versus 113±14 ms, P=0.04), of AH interval during both sinus rhythm (92±13 versus 76.8±8 ms, P<0.01) and atrial pacing at 400 ms (102±13 versus 91±9 ms, P<0.01), and of AV node Wenckebach cycle length (230±19 versus 213±24 ms, P<0.01), with no changes in the control group. The RR interval during induced AF 28 days after injections was 24% longer in ADF-treated group compared with controls (488±120 versus 386±116 ms, P<0.001). Histological analysis revealed presence of ADF-labeled cells in the AV nodal area at 28 days. Transient accelerated junctional rhythm during injections, and transient nocturnal Mobitz I AV conduction occurred early postinjection in both groups. Conclusions— Cells survived for 4 weeks and significantly slowed AV conduction and ventricular rate in acutely induced AF. Critically, despite a large number of injections in the AV nodal area and marked effects on AV conduction, AV block did not occur. Further studies are necessary to determine the clinical feasibility and safety of this strategy for ventricular rate control in AF.